Economic development in South Asia - SANEI Conference 2002 Dhaka, Bangladesh); Khan, Mohsin S.; South Asia Network of Economic Research Institutes (New Delhi Tata McGraw-Hill, 2005)
Contributed articles on economic policy in South Asia presented at Fourth Annual SANEI Conference at Dhaka, in 2002 initiated by South Asia Network of Economic Research Institutes.
Economic development in South Asia : an overview / Mohsin S. Khan -- Exports and economic growth in South Asia / A.R. Kemal, Musleh ud Din, Usman Qadir -- Informal trade in India, Nepal, and Sri Lanka / Nisha Taneja ... [et al.] -- Reforms and power sector in South Asia : scope and challenges for cross-border trade / Mahendra P. Lama, Q.K. Ahmad, Mohan Man Sainju -- The economics of pensions and social security in South Asia / S. Irudaya Rajan ... [et al.] -- Causes of fertility decline in India and Bangladesh / S. Mahendra Dev, K.S. James, Binayak Sen -- Gender and local governance : a new discourse in development / Ishrat Shamim, Ranjana Kumari -- An economic
Keywords: South Asia -- Economic policy -- Congresses; South Asia -- Economic conditions -- Congresses